2014
DOI: 10.1016/j.avsg.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Oxygen Reverses Hypoxia-induced Smooth Muscle Cell Proliferation by Modulating HIF-alpha and VEGF Levels in a Rabbit Arteriovenous Fistula Model

Abstract: OBJECTIVES Numerous mechanisms for the formation of intimal hyperplasia have been proposed but none have been proven or accepted. Our research focuses on the potential role of Hypoxia Inducible Factors (HIFs), VEGF, and PDGF as well as the ERK, PI3-K/AKT pathway in hypoxia mediated intimal hyperplasia processes. We hypothesize that HIF and VEGF will be down regulated with supplemental oxygen in our arteriovenous fistula rabbit model. METHODS Rabbits were randomized into different experimental groups with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 27 publications
2
40
0
2
Order By: Relevance
“…In brief, cells were cultured in a 96-well plate for 24 h and pulse-labeled with BrdU for 4 h according to the manufacturer's instructions. The BrdU label in the DNA was detected using a peroxidase and FITC-conjugated anti-BrdU second antibody subjected to immunodetection and immunofluorescence assays (24). For peroxidase-conjugated anti-BrdU immunodetection, the values of relative proliferation was quantified with a peroxidase substrate and measured at 370 nm with a wavelength of 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, cells were cultured in a 96-well plate for 24 h and pulse-labeled with BrdU for 4 h according to the manufacturer's instructions. The BrdU label in the DNA was detected using a peroxidase and FITC-conjugated anti-BrdU second antibody subjected to immunodetection and immunofluorescence assays (24). For peroxidase-conjugated anti-BrdU immunodetection, the values of relative proliferation was quantified with a peroxidase substrate and measured at 370 nm with a wavelength of 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier work in rabbits had shown that supplemental oxygen reduces IH after stent deployment [107]. Additional work in rabbits indicated that supplemental oxygen inhibits IH and SMC proliferation after creation of an arterio-venous fistula and prolongs patency [114].…”
Section: Stent Hypoxiamentioning
confidence: 99%
“…Ischemia and the release of ROS activate early response elements such as hypoxia-inducible factor 1-alpha (HIF-1α) and immediate-early responsive gene (IEX-1). [29][30][31] These in turn activate endothelial cells (ECs), inflammatory cells, and vascular SMCs. HIF-1α, ROS, and hypoxia have been shown to upregulate vascular endothelial growth factors (VEGFs), which increase inflammation and promote EC proliferation.…”
Section: Hypoxiamentioning
confidence: 99%
“…25,30,[32][33][34][35][36] Hypoxia also activates platelet-derived growth factor, which has been shown to increase myofibroblasts. 13,31,35,37 These are the main proliferative changes that occur. However, cytokines such as VEGF-A, IEX-1, HIF-1α have also been shown to propagate inflammation, which can subsequently induce proliferation resulting in a dangerous positive feedback loop.…”
Section: Hypoxiamentioning
confidence: 99%